The Role of Mechanosensitive Piezo Channels in Chronic Pain - Wan Y; Zhou J; Li H (Journal of Pain Research)
Yantong Wan,* Jieshu Zhou,* Hao Li Department of Anesthesiology, West China Second University Hospital, Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, Ministry of Education, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hao Li, Department of Anesthesiology, West China Second University Hospital, Sichuan University, Chengdu, Sichuan, 610041, People’s Republic of China, Tel +86-028-85503753, Email lihao0510@163.comPurpose of Review: Mechanosensitive Piezo channels are ion channels activated by mechanical stimuli, playing a crucial role in mechanotransduction processes and mechanical hypersensitivity. When these channels are subjected to mechanical loading, membrane currents rise instantaneously, depolarizing and activating voltage-gated calcium channels. This results in an increase in intracellular Ca2+, which contributes to heightened sensitivity to mechanical stimuli. This review delves into the characteristics and mechanisms of Piezo channels in chronic pain.Recent Findings: The findings suggest that Piezo channels are integral to the occurrence and development of chronic pain, including neuropathic pain, visceral pain, musculoskeletal pain, headache or orofacial pain, and inflammatory pain. Piezo channels significantly impact pain perception and transmission. These channels’ critical involvement in various pain types highlights their potential as promising targets for chronic pain therapy.Summary: This review discusses the role of Piezo channels in chronic pain. By understanding these pain mechanisms, new therapeutic strategies can be developed to alleviate chronic pain, offering hope for patients suffering from these debilitating conditions.Keywords: Piezo channel, mechanotransduction, mechanical hypersensitivity, chronic pain